Financing Sources of Tasks in the Field of Environmental Protection in Poland – an Overview of Applied Solutions - Anna Barczak; Ewa Kowalewska (Prawo Budżetowe Państwa i Samorządu)
A significant development of investments to protect environment has been noticed in the past ten years in Poland. The purpose of this paper is to present financial instruments which are the financing sources of the tasks in the field of environmental protection. It has been noticed their special role. It has also been emphasized that without the participation of all those instruments would be impossible to achieve environmental plans and priorities, projected in the National Environmental Policy and local environmental programs. This study is a comprehensive analysis of the normative material and ideas presented in the literature of financial and environmental law.